Do Indonesian Students Favour Native English Speakers Teachers in Their Classes?: A Survey Study on Indonesian EFL Students - Moh. Hilman Fikri; Abd. Syakur; Gigih Dwi Ananto (SAINTIS Publishing, 2025)
The creativity of English L2 speakers exploiting the language provoked the researcher to explore students' preference for having native English speaker teachers (NESTs) and non-native English speaker teachers (NNESTs) in their classes. Thus, the current study aimed to explore EFL students' perceptions of native English speaker teachers (NESTs) and non-native English speaker teachers (NNESTs) teaching English in a class. The study recruits a hundred EFL students across Malang, East Java, piloting survey design on the basis of a convenience sampling technique. In general, the study unpacked the students' positive attitudes toward NNESTs. They agreed that they should have NNESTs at primary, secondary, and university levels. However, they suggested that NESTs should teach speaking and pronunciation. In addition, the respondent preferred having both NESTs and NNESTs in a class to be more engaging and stress-revealing. Therefore, initiating a class team teaching between NESTs and NNESTs is paramount for the stakeholders to be taken into account.